Development of an algorithm with temporary cryptographic security for encrypting video stream from an unmanned aerial vehicle - Kovalchuk, Liudmyla; Davydenko, Anatolii; Klymenko, Tatiana; Nedashkivska, Arina; Hilgurt, Serhii (Eastern-European Journal of Enterprise Technologies, 2025)
This study considers the process that protects a video stream transmitted from the onboard video camera of an unmanned aerial vehicle (UAV) to a ground station in the front and near-front zones. The specificity of the task set is predetermined, on the one hand, by the limited computing resources of onboard equipment, which must encrypt an intensive data stream in real time, and, on the other hand, by the relatively short life span of UAV under combat conditions (especially for FPV kamikaze drones) ranging from 10 minutes to several days. Most known works in this field consider algorithms focused on application in other settings, with the main efforts aimed at achieving maximal cryptographic security. Unlike the technological advancements highlighted in the available literature, this study has managed to solve the specified problem by taking into account its specific features and utilizing a certain trade-off between the speed and resource intensity of the algorithm, on the one hand, and its security, on the other. The result was achieved through a detailed comparative analysis and categorization of the closest solutions in terms of characteristics, which is the largest part of the study. Based on its results, the PRESENT algorithm was chosen as the first approximation. The proposed solution is based on the use of a modification of this algorithm reduced to 16 rounds in counter mode. Analysis of the resulting solution reveals that its cryptographic security requires more than 2 months of computational work when implementing the best attack, i.e., the security of the algorithm is reasonably acceptable. For practical application of the theoretical results, it is necessary to carefully check the properties of the proposed solution implemented in the equipment under field conditions, as close as possible to combat operations, and, if necessary, to make the necessary adjustments